The Design and Optimization of Ceramide NP-Loaded Liposomes to Restore the Skin Barrier - Hümeyra Şahin Bektay; Ali Asram Sağıroğlu; Kübra Bozali; Eray Metin Güler; Sevgi Güngör (MDPI AG, 2023)
The impairment of skin integrity derived from derangement of the orthorhombic lateral organization is mainly caused by dysregulation of ceramide amounts in the skin barrier. Ceramides, fatty acids, and cholesterol-containing nano-based formulations have been used to impair the skin barrier. However, there is still a challenge to formulate novel formulations consisting of ceramides due to their chemical structure, poor aqueous solubility, and high molecular weight. In this study, the design and optimization of Ceramide 3 (CER-NP)-loaded liposomes are implemented based on response surface methodology (RSM). The optimum CER-NP-loaded liposome was selected based on its particle size (PS) and polydispersity index (PDI). The optimum CER-NP-loaded liposome was imagined by observing the encapsulation by using a confocal laser scanning microscope (CLSM) within fluorescently labeled CER-NP. The characteristic liquid crystalline phase and lipid chain conformation of CER-NP-loaded liposomes were determined using attenuated total reflectance infrared spectroscopy (ATR-IR). The CER-NP-loaded liposomes were imagined using a field emission scanning electron microscope (FE-SEM). Finally, the in vitro release of CER-NP from liposomes was examined using modified Franz Cells. The experimental and predicted results were well correlated. The CLSM images of optimized liposomes were conformable with the other studies, and the encapsulation efficiency of CER-NP was 93.84 ± 0.87%. ATR-IR analysis supported the characteristics of the CER-NP-loaded liposome. In addition, the lipid chain conformation shows similarity with skin barrier lipid organization. The release pattern of CER-NP liposomes was fitted with the Korsmeyer-Peppas model. The cytotoxicity studies carried out on HaCaT keratinocytes supported the idea that the liposomes for topical administration of CER-NP could be considered relatively safe. In conclusion, the optimized CER-NP-loaded liposomes could have the potential to restore the skin barrier function.